Adaptive Traffic Prioritization Algorithm Over Ad Hoc Network Using IEEE 802.11e - Anuar, Ammar (2016)
This thesis proposes an adaptive traffic prioritization algorithm over ad hoc network using IEEE 802.11e standard that defines a set of Quality of Service enhancements for wireless LAN applications through modifications to the Media Access Control (MAC) layer. The IEEE 802.11e standard aims to provide enhancements that allow traffic with specific requirements to be treated differently from normal traffic. Enhanced Distributed Channel Access (EDCA) is a fundamental and mandatory contention-based channel access method of IEEE 802.11e which delivers traffic based on differentiated Access Category (ACs). Each AC has its own queue and set of EDCA parameter values. Although IEEE 802.11e has been widely implemented in commercial hardware, the EDCA parameters are normally preset with some default values recommended by the standard. By default, the values of EDCA parameters are not open for changes. This has limited the performance as from literature review, a proper EDCA parameter manipulation will improve the network throughput performance. However, most existing research works on IEEE 802.11e EDCA parameter optimization are done either analytically or in simulated environments and hence are unable to provide its effectiveness in realistic scenarios. This is largely due to the several hurdles associated with real-life implementations which prohibit them to do so, such as hardware limitations, software restrictions, coding bugs in the wireless cards driver and so on.These challengess form part of the motivations behind this work. This thesis first investigates the impacts of EDCA parameters on the network performance and link conditions using open source software and commercially available hardware in ad hoc mode. An adaptive prioritization scheme (APS) is then proposed. The results obtained show that the proposed APS algorithm can improve the single-AC throughput performance up to 10.82% when compared to static EDCA. In dual-AC scenario, APS can improve the throughput performance up to 9.93% as compared to static EDCA, while another scheme in existing literature, R-AIFSN shows inconsistency in throughput performance. It is also found that the improvement is more significant in terms of the queue occupancy.